If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(-10+10g)=3(9-9g)
We move all terms to the left:
3(-10+10g)-(3(9-9g))=0
We add all the numbers together, and all the variables
3(10g-10)-(3(-9g+9))=0
We multiply parentheses
30g-(3(-9g+9))-30=0
We calculate terms in parentheses: -(3(-9g+9)), so:We get rid of parentheses
3(-9g+9)
We multiply parentheses
-27g+27
Back to the equation:
-(-27g+27)
30g+27g-27-30=0
We add all the numbers together, and all the variables
57g-57=0
We move all terms containing g to the left, all other terms to the right
57g=57
g=57/57
g=1
| 69*t/60=60*(t-10)/60 | | x=14/14x+14 | | 3.8(n-16)+4.9=1.1 | | 21=x9 | | 5z+8=180 | | 216^x=6^{x+10} | | -1/5w=-20 | | 1.3x=7x+12 | | -3(-5q-10)=8q+2 | | 2=3x/12 | | -(-22+5y)+2y=13 | | √3x₊4=7 | | 36=24/11s | | 2t+2-3=19 | | 5x-20+2x=180° | | 16=3x/12 | | 3x-2=10,3x=12 | | 36/24=x/26 | | (-22+5y)+2y=13 | | 3x-2=103x=12 | | 3n=4=7= | | 12x+15=8x-5 | | 4K+7=2(6k-14)+51 | | (m/2)=17 | | 2(8v+2)-10v=-4(-4v+9) | | 50/24=x/12 | | 3x+7=−4x−21 | | x=-8=23 | | 3x+2+4x-8=64 | | 2/5v+13=17 | | 14=1/3x+4;27 | | −2+x+44=−x+4x |